2021
DOI: 10.12973/ijem.7.1.79
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Instructional Autonomy Practices of Science Teachers

Abstract: Contemporary studies related to teacher autonomy mostly deal with research into how autonomy is perceived by teachers and which variables it is associated with. On the other hand, there are very few studies dealing with how teachers' instructional autonomy over the curriculum is reflected in the education process. The aim of this study is to reveal in depth the practices carried out in the context of instructional autonomy by science teachers who have different levels of autonomy. The study is based on data ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Based on this result, which shows that the study findings are consistent, it can be said that it is difficult for a teacher to manage the class effectively based on a single power in crowded classes. The finding indicating that teachers in crowded classrooms experience problems in classroom management in many studies confirms this view (Balay & Sağlam, 2008;Demir & Ersöz, 2016;Yaman, 2010;Yolcu & Akar-Vural, 2021). These problems may have pushed teachers to use a combination of personal traits such as personal power and charismatic power and types of power based on teacher-student interaction.…”
Section: Discussionmentioning
confidence: 71%
“…Based on this result, which shows that the study findings are consistent, it can be said that it is difficult for a teacher to manage the class effectively based on a single power in crowded classes. The finding indicating that teachers in crowded classrooms experience problems in classroom management in many studies confirms this view (Balay & Sağlam, 2008;Demir & Ersöz, 2016;Yaman, 2010;Yolcu & Akar-Vural, 2021). These problems may have pushed teachers to use a combination of personal traits such as personal power and charismatic power and types of power based on teacher-student interaction.…”
Section: Discussionmentioning
confidence: 71%
“…These 600 people are interviewed in a Multiple Mini-Interview, during which a final admission decision is made, based on their GPA and test scores. This mini-interview is an innovative technology in medical education, replacing the standard interview since 2002 (Yolcu & Akar-Vural, 2021). The essence of the mini-interview is as follows.…”
Section: Features Of Admission and Selection Of Candidates For Medica...mentioning
confidence: 99%
“…The duration of the exam is 2 days. Based on the results of the exam, future physicians receive a license to practice medicine, and the exam process is overseen by the Medical Council of Canada (Yolcu & Akar-Vural, 2021).…”
Section: Schedule Of Students In a Medical Education Settingmentioning
confidence: 99%
“…The use of digital technology in the educational process is largely dictated by educational institutions. At the same time, the study of Yolcu & Akar-Vural, (2021) indicated that teachers with a higher level of teaching autonomy achieve better learning outcomes for their students (Drobotenko, Duka, Kurdumanova, Chekaleva, Sharov, & Dyrka, 2019). The school climate and the teacher-student relationship pattern also strongly influence students' motivation to learn (Dincer, 2021).…”
Section: Introductionmentioning
confidence: 99%